Electronic-Based Government System (SPBE) Policy in Bitung City - Emor, Christ Kevin; Masengi, Evi E.; Tumbel, Goinpeace H. (International Journal of Information Technology and Education, 2024)
This study aims to (1) Describe, analyze, and explain the Implementation of the Electronic-Based Government System Policy in Bitung City. (2) Describe, analyze, and explain the determinant factors in implementing the Electronic-Based Government System Policy in Bitung City. This study uses a qualitative method with a narrative study research approach. This approach is carried out to provide an overview through detailed explanations by informants, compare them with existing data, and review existing documents related to the Implementation of the Electronic-Based Government System Policy (SPBE) in Bitung City. The study’s results indicate that the implementation of SPBE in Bitung City has positively impacted the efficiency and transparency of public services. However, several challenges must be overcome, such as increasing HR competency, improving infrastructure, and optimizing the budget. More even socialization and increasing coordination between OPDs are also needed to ensure maximum utilization of SPBE services. The implementation of SPBE in Bitung City is an ongoing process that requires adjustments and improvements so that the community can access all public services effectively and evenly.